Contextual Storytelling for English Speaking with Local Wisdom: A Development Study - Muhammad Hassan; Donny Adiatmana Ginting; Fernando De Napoli; Rosmen (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to explore the effectiveness of contextual storytelling in enhancing English speaking skills among students, with a particular focus on incorporating local wisdom from North Sumatra. The study was conducted with English Education students at STKIP Al Maksum, specifically targeting second-semester students across two classes. The research employed a developmental approach, using a combination of qualitative and quantitative methods. The participants engaged in storytelling activities based on local wisdom, integrating both digital storytelling tools and traditional narratives to improve their speaking abilities. Data were collected through pre- and post-tests, student feedback surveys, and observations. The results demonstrated significant improvement in students’ fluency, pronunciation, vocabulary usage, and coherence in English speaking. Additionally, students showed a deeper connection to their cultural heritage and reported increased confidence in sharing local stories in English. The integration of digital tools, such as video and audio recordings, proved highly effective in enhancing student engagement and creativity. Overall, the findings suggest that the contextual storytelling model, rooted in local wisdom, is an innovative and effective method for improving students’ English speaking skills while fostering cultural awareness. This study contributes valuable insights to the field of English language teaching by demonstrating the positive impact of incorporating local culture and digital storytelling in language learning.